The EDEN ISS mobile test facility microbiome changes by cleaning and continued use - Gaiser, Luis; Beblo-Vranesevic, Kristina; Van Houdt, Rob; Fahrion, Jana; Gillet de Chalonge, Louise; Bunchek, Jess M.; Zabel, Paul; Schubert, Daniel; Rettberg, Petra (Frontiers in Microbiomes, 2025)
IntroductionBioregenerative life support systems (BLSS) utilizing plants and/or microorganisms to provide the crew of a spacecraft with food, clean water, breathable air, and other amenities are likely to form key components of future long-distance spaceflight missions. Extensive testing and validation of such technologies are necessary before they can be implemented. EDEN ISS was a platform in Antarctica that tested various plant cultivation technologies for a BLSS. To ensure the continued operation of a BLSS, it is vital that plants remain healthy, which necessitates the monitoring of the plant production facility microbiome to ensure that pathogens are detected early and countermeasures can be engaged.MethodsSwab surface samples collected in the EDEN ISS Mobile Test Facility (MTF) during different campaigns were used to estimate the bioburden of the various surfaces via viable count. Isolates obtained from the cultivation of the surface samples were identified via partial 16S rRNA gene sequencing. Additionally, 16S amplicon sequencing was performed on DNA extracted directly from the swab samples to characterize the microbiome.Results and discussionThe results revealed that the bioburden of the different sampling positions was not significantly reduced by cleaning, indicating that the employed cleaning regime was unsuited in its current form to adequately lower the bioburden. Identification of the isolates, as well as the full microbiome, revealed mostly environmental genera. However, in both cases, genera containing plant as well as human pathogens, like Pseudomonas and Acinetobacter, were identified and accounted for up to 16.1% of all reads for a sampling condition in the case of Pseudomonas. The two sets of sequencing data had little overlap, with Rhodococcus and Microbacterium being the only genera shared between all sampling conditions and sequencing approaches, and emphasized different aspects of the MTF microbiome, highlighting the advantages of using a combined approach to obtain a more complete picture of the microbiome composition.